The Poliarnaia Kochegarka Newspaper as a Source on the Soviet Mining on Spitsbergen in the 1930–1980s: A Brief Bibliographical Survey - Portsel, Aleksandr (Nordlit, 2020)
Copies of the Poliarnaia kochegarkanewspaper, published by the Russian/Soviet mining trust Arktikugol and stored in the State Archive of the Murmansk Region (GAMO), contain a wealth of material which emerged after a systematic coverage, for nearly half a century, of various aspects of the development of the Svalbard (Spitsbergen) archipelago, from Stalin’s times to the late Soviet period. In the newspaper, one can find a wide range of topics and genres, from the official publications both at the state and the local levels to sketches of polar dwellers’ everyday life. Poliarnaia kochegarka’s articles help readers to trace the development of Arktikugol’s capacities and the formation of normal living conditions in the Soviet Arctic settlements on the archipelago. Poliarnaia kochegarkaalso contains many observations on the Norwegian mines on Svalbard. Its particular interest, however, consists in various historical surveys and the information about the international contacts on the archipelago.